2022
DOI: 10.3389/fpubh.2022.751985
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Functional Limitations and Incident Cardiovascular Diseases and All-Cause Mortality Among the Middle-Aged and Older Adults in China: A Population-Based Prospective Cohort Study

Abstract: BackgroundThe prevalence of functional limitations is relatively high among the middle-aged and older adults. However, the contribution of functional limitations to subsequent incident cardiovascular diseases (CVD) and death is unclear. This study aims to examine the association between functional limitations and incident CVD and all-cause mortality among the middle-aged and older adults.MethodsThis is a nationally representative prospective cohort study. Participants were middle-aged and older Chinese adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Special attention should be given to middle-aged and older person with ADL disability to prevent the incidence of their frailty. Besides, ADL disability is one independent risk factor for 7 years mortality in middle-aged and older adults in China ( 84 ), and ADL skills can facilitate successful aging ( 85 ). Frailty serves as a strong predictor for disability in ADL, while disability in ADL is also a strong predictor of frailty among middle-aged and older population.…”
Section: Discussionmentioning
confidence: 99%
“…Special attention should be given to middle-aged and older person with ADL disability to prevent the incidence of their frailty. Besides, ADL disability is one independent risk factor for 7 years mortality in middle-aged and older adults in China ( 84 ), and ADL skills can facilitate successful aging ( 85 ). Frailty serves as a strong predictor for disability in ADL, while disability in ADL is also a strong predictor of frailty among middle-aged and older population.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously demonstrated that functional health literacy is independently predictive of mortality among adults hospitalized for cardiovascular events, presumably through an inability to manage the complex medication prescriptions and dietary requirements associated with cardiovascular disease. 17,47 Similarly, it has long been established that patient-reported exercise frequency is predictive of mortality among adults with increased risk for cardiovascular disease, though the precise amount of leisure time physical activity needed to confer a mortality benefit remains a source of ongoing investigation. 48 However, our cohort added to these data by using a wide range of validated measures of disease self-management, followed patients for an extended period of time, and adjusted for numerous demographic and clinical characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to point out that study subjects had mean ADL and IADL scores indicative of preserved functional abilities. Elderly people with diabetes are at increased risk of frailty and disability [ 33 , 34 ], which in turns are associated to with adverse health outcomes, including mortality risk in older subjects [ 35 ]. In addition, a lower functional ability can translate into a greater tendency to rely on caregivers and therefore it may influence LOC domains.…”
Section: Discussionmentioning
confidence: 99%